Persistently raised intraocular pressure following extracapsular cataract extraction. Issue 5 (May 1990) - David, R.; Tessler, Z.; Yagev, R.; Briscoe, D.; Biedner, B. Z.; Gilad, E.; Yassur, Y.
Abstract : In this population based study we have reviewed the files of all patients who underwent an extracapsular cataract extraction (ECCE) between 1984 and 1987, were normotensives prior to surgery, and were followed up for at least 10 months after the ECCE. From a total of 1047 operations 746 qualified for the inclusion criteria; of these, 16 (2.1%) were found to have a consistently raised intraocular pressure (greater than 21 mmHg) on more than two occasions) at four months or later after surgery and throughout at least a six-month period. An increased incidence of secondary aphakic glaucoma was associated with anterior chamber IOL implantation (p less than 0.001) and posterior capsule rupture (p less than 0.01), but not with any of the other variables examined (age, sex, surgeon).